Variability in exercise physiology: Can capturing intra-individual variation help better understand true inter-individual responses? - Chrzanowski-Smith, O.J.; Piatrikova, E.; Betts, J. A.; Williams, S.; Gonzalez, J. T. (European Journal of Sport Science, 2020)
1. Introduction 2. What is intra-individual variation? 3. Accounting for intra-individual variation to determine whether true inter-individual responses to an intervention exist 4. The consideration of intra-individual variation prior to a training programme to explain true inter-individual responses 5. Conclusion